The Assessment of water quality modeling using GIS and Qual2K simulation analysis for the Klang River basin / Alaa Eldin Mohamed Elamin Elnour Ahmed - Alaa Eldin Mohamed Elamin, Elnour Ahmed (2014)
The amplified pressure on urban areas in Malaysia has been generated by rapid growth in the manufacturing field, especially in the Klang River Basin, which is the most densely populated area of the country. The basin located within two states in Malaysia, i.e. Selangor and Kuala Lumpur. It drains an area of 1,288 square Kilometers. The water quality of the Klang River basin is significantly degraded due to human activities as well as urbanization. As the two states are undergoing tremendous development, Klang River is subjected to pollution from point and non-point sources. Normally the evaluation of the overall river water quality status is represented by a water quality index (WQI), which consists of six parameters, namely dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solids (SS), ammoniacal nitrogen (AN) and pH. The modeling of the water quality was often employed as a supporting tool for the assessment of the aquatic environment, and the calculated results provided valuable information for improvement water quality management. The water quality modeling was coupled with geographical information system (GIS) to determine the strategy for the water resources management. In this study, GIS tools were used to develop the digital spatial map for the Klang River basin and build its database, as well as to prepare the required spatial data to run the water quality model. The Qual2K was used as a simulation model to predict and evaluate the status of the water quality in Klang River main stem. Two water quality parameters have been chosen for modeling, i.e. DO and BOD. In addition, three model scenarios were simulated to assess the impact of the point sources on the quality of KlangRiver water. Furthermore, the model output has been linked to the GIS environment for better analyzing, viewing and evaluation of the results. The results showed that the developed digital spatial map is an effective map that connects the spatial data of the features with their tabular databases, which make it easy to analyze the data for better results that help for decision-making. It proved that it is more powerful, convenient, interactive and efficient than the traditional paper map. This digital map is a physical map that at any time it can easily be edited and modified. The simulated results for the current condition indicate that DO upstream of the Klang River’s main stem varies between classes I and II, while BOD varies between class II and III. The class of DO decreased from mid-stream toward downstream where it recorded a class IV. The BOD was recorded as class IV at mid-stream and improved downstream to class III. Moreover, the simulated results of the three scenarios indicated that the Sewerage Treatment Plants (STPs) are the main contributor to the source of DO and BOD pollution to the river system. Omitting Sewerage Treatment Plants (STPs) with standards A and B caused an increase in DO amounts (ranging between 0% and 40.5%), whereas the BOD amounts decreased between 0% and 49.4%. By linking the model output with the GIS platform, the classes of the river quality in terms of DO and BOD were represented clearly along the Klang River catchment. In addition, the results helped for easy analyzing and evaluation of the river quality. These results can be used as a tool in designing a decision support system.